Process Development for the Effective Extraction of Curcumin from Curcuma Longa L (Turmeric) - Muthukumar P, Vinosh; M, Vaishnavi; S, Theepapriys; A, Saravanaraj (International Journal of Engineering and Technology, 2018)
Curcumin, the active, light sensitive agent, found in significant amounts in Curcuma longa L, is a potential therapeutic agent, possessing various pharmaceutical and industrial uses. The present extraction techniques, that are in application for many decades suffer from many economical and environmental demerits. This work is a prospective and noteworthy step towards conquering those disadvantages by means of optimizing the extraction process parameters and developing an energy efficient, environment friendly and economical process. In this study, various organic solvents were tested for their ability of curcumin extraction an concluded that acetone is most efficient. The process parameters like time, temperature and particle size were investigated and the minimum volume and concentration of solvent required were determined. Three potential pre-treatment process were analyzed for their capability to effectively distort the turmeric structure and aid in increasing the overall efficiency of the process. It was found that, employment of a mechanical distortion method by microwave assistance, and further followed by chemical disintegration, by means of enzymatic treatment, resulted in high attainable efficiency.Â Â